Childhood rosacea: a case report and a review of terms on a commonly missed diagnosis. - Patsatsi, A.; Kyriakou, A.; Kalabalikis, D.; Trakatelli, M.-G.; Nasr, A.; Efstratiou, I.; Sotiriadis, D. (European Journal of Pediatric Dermatology, 2010)
Childhood rosacea is often misdiagnosed resulting in a chronic course under a variety of unsuccessful treatment schemes. A 5-year-old boy was admitted with a papular eruption around the eyes, mouth and neck. There was no preceding history of corticosteroid use prior to the onset of the eruption, four months ago. Under the diagnosis of atopic dermatitis, the patient was treated with steroids, pimecrolimus and emollients without any response. One of the new neck lesions was biopsied and histology revealed findings of a granulomatous rosacea lesion. Application of topical metronidazole 0.75% induced shortly a significant improvement. In this report we review the current literature and discuss the quandary regarding the different names of this form of rosacea.